Laws of the Government of New-Castle, Kent and Sussex Upon Delaware 171 (1741) - (:unkn) unknown (My University, 1740)
"That every Freeholder and taxable Person residing in this Government (except such as are hereafter excepted) shall, on or before the First Day of March next, provide himself with the following Arms and Ammunition: One well fixed Musket or Firelock, one Cartouch-Box, with Twelve Charges of Gun-Powder and Ball therein, and Three good Flints, to be approved of by the Commanding Officer of the respective Company to which he belongs, and shall be obliged to keep such Arms and Ammunition by him, during the Continuance of this Act...."
Keywords: REQUIRED POSSESSION